La educación en valores potencializada desde la familia y su incidencia en el rendimiento académico de los alumnos de cuarto, quinto, sexto y séptimo año de educación básica de la escuela Uruguay de la ciudad Amaluza, cantón Espíndola , durante el período lectivo 2011-2012 - Jumbo Sarango, Marisol de Fatima (2013)
The research work called potentiated VALUES EDUCATION FROM FAMILY AND ITS IMPACT ON THE ACADEMIC PERFORMANCE OF STUDENTS FOURTH, FIFTH, SIXTH AND SEVENTH YEAR BASIC EDUCATION SCHOOL "URUGUAY" THE PARIS AMALUZA, CANTÓN ESPÍNDOLA. DURING THE PERIOD 2011-2012.Se LECTIVO raised a general objective and practical Research the type of power family values and academic performance achieved by the students of the school "Uruguay" of the parish of Amaluza, Cantón Espíndola, during the period 2011-2012. The specifics are: Determine what type of values are enhanced from the family to the students of the School "Uruguay" and how they determine the personal development of the same. Check for empowerment practice from family values affects the academic performance of students of the School "Uruguay". Design, develop, and evaluate a pedagogical allowing promote, integrate, develop various forms of practices based on the formation of values in children of the fourth, fifth, sixth and seventh grades. After the work was reached the following conclusions: The practice of values that teaches children of the School "Uruguay" by the family affects the academic performance of children because 65% of respondents answer always is strengthening moral, ethical, civic, intellectual, social and other. And 100% agree that good practice is the main values impact on the academic performance of children, from the observations made children of the school "Uruguay" a large number of them practice the values of responsibility, solidarity, creativity and critical respect, discipline and personal presentation, likewise there is another group that still must continue to reaffirm these values by parents, the use of the manual "Stories and fables of yesterday ... today values are" les allow students to practice values not only in school but also in the family. After the present investigation the following is recommended: That the families of the children in the school "Uruguay" continue promoting the practice of values, as these affect the academic performance of their children's children influenced by parents forming social consciousness, developing attitudes intellectual, active communication, development of empathy and solidarity with others linking and mainstreaming with adults, especially in building values by taking into account their active role in society, is suggested that parents be made aware of family responsibility with respect to, for potential values education and facilitate manual neighboring schools to be incorporated into the practice of values so that we can begin a process of transformation in the behavior of students. It is noteworthy that the potentiation of the values positively affects the academic performance of children.